VIOLÊNCIA E REDE DE ATENDIMENTO ÀS MULHERES EM ALAGOAS E SERGIPE - Pereira dos Santos Vieira, Ticiane; da Silva Lima, Jaqueline; Simões Barreto, Elvira (Serviço Social em Debate, 2024)
It is proposed a reflection on the Women’s in Violence Situation Service Network (in Brazil, RAMSV) in Alagoas and Sergipe, from analyzes based on the critical-dialectical method. The brief historical review on the expressions of violence against women in Brazil and about feminist struggles leads to the apprehension of the State’s systematic interventions captured by the logic of reform under the aegis of multilateral organizations. Under this analytical perspective, with an empirical cut in the states of Alagoas and Sergipe, it is possible to observe the advances in the construction of the RAMSV, however, it is notable that there are areas that have not yet been contemplated, a fact that expresses the limits imposed by the neoliberal logic of management of the State which is also sustained by oppressive relations of class, gender and ethnicity.